Site index - The Editors, - (Nordic Archaeological Abstracts - NAA, 1990)
The specific names of sites are listed for castles, churches, monasteries, towns, and well-known find localities. The name of the relevant county, district, or region according to the map is always listed, except when the paper deals with a larger area. General surveys may be found under SURVEY in the Subjct index. Outside the Nordic area, the name of the country is listed, as are well-known find localities and sites. A guide to the alphabetical order is given in the Author index.